Expression of organic cation transporter 1 (OCT1): unique patterns of indirect regulation by nuclear receptors and hepatospecific gene regulation. (2nd April 2016) - Hyrsova, Lucie; Smutny, Tomas; Trejtnar, Frantisek; Pavek, Petr
Abstract: The organic cation transporter 1 (OCT1) is the dominant carrier of organic cationic drugs and some positively charged endogenous compounds into hepatocytes. OCT1 has unique expression pattern. It has the highest expression among drug transporters in normal human hepatocytes with large interindividual variability, but it has negligible expression in other tissues or their tumors. Nowadays, it is clear that the regulation of SLC22A1 gene encoding OCT1 transporter is rather complex and that transactivation with hepatocyte nuclear factor 4α (HNF4α) and CCAAT-enhancer-binding protein (C/EBPs) transcription factors as well as epigenetic regulation contribute to its unique hepatocyte-specific expression pattern. Unfortunately, species- and tissue-specific regulation of OCT1 and its orthologs as well as significant down-regulation in most immortalized cell lines hamper the study of SLC22A1 gene regulation. In the current review, we summarize our current understanding of human OCT1 transporter hepatic gene regulation and we propose potential post-transcriptional regulation by predicted miRNAs. We also discuss in detail recent findings on indirect regulation of the transporter via farnesoid X receptor (FXR), glucocorticoid receptor and pregnane X (PXR) receptor, which point out to potential novel mechanisms of xenobiotic-transporting and drug-metabolizing proteins regulation in the human liver as well as to potentially novel drug–drug interaction mechanisms. We also propose that comprehensive understanding of mechanisms of SLC22A1 gene regulation could direct research for other drug transporters and drug-metabolizing enzymes highly expressed in hepatocytes and controlled by HNF4α or other liver-enriched transcription factors.